Literatur Riview Urinary Tract Infection in Children: Infeksi Saluran Kemih pada Anak - Angela Angela (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Urinary tract infection is an infection that is mainly found in children and can affect the upper and lower parts of the urinary tract. Urinary tract infection is one of the most common causes of fever experienced by children, especially girls. The infection is classified into upper urinary tract infections (pyelonephritis), lower tract (cystitis), and asymptomatic bacteriuria. This study aims to explore the symptoms, diagnosis, and management of UTI in children. It was found that urinalysis and urine culture were needed in diagnosing UTI by considering urine sampling. Urinalysis could diagnose UTI if positive esterase or nitrite leukocytes and urine culture were found. Managing urinary tract infections in children could be challenging because of the vague and non-specific symptoms. However, it must consider the level of resistance, the child's age, the location of the infection, the severity, and the antibiotics given. The study found that the treatment of UTI was carried out to prevent sepsis in children, where antibiotics were still one of the primary therapies to treat urinary tract infections in children. The use of antibiotics in children with Vesicoureteral Reflux (VUR) aimed to reduce the recurrence of urinary tract infections, so a low dose of antimicrobials was recommended.